A Robust Approach in Nonlinear Fuzzy Control of Chemical Process (Chemical Engineering Research Bulletin, 2013)
This paper presents a novel and robust fuzzy controller. The controller has conventional fuzzy inputs membership functions but has Bang-bang subsequent outputs membership functions. The controller on-line adaptation is accomplished by tuning and self-organizing the input membership functions. New rules and membership functions are created on-line with sliding mode control knowledge base rules. The systems closed loop stability is assured for each rule, which is stable in sense of Lyapunov. The suggested controller performance and analysis is confirmed by simulation of well know non-linear benchmark problems. DOI: http://dx.doi.org/10.3329/cerb.v16i1.12720 Chemical Engineering Research Bulletin 16(2013) 45-60